Pengaruh Harga, Kualitas Produk dan Brand Equity terhadap Keputusan Pembelian di Waroeng Makan â€œSpesial Sambalâ€ Tembalang, Semarang - Parhusip, Crystin Ayomi; Waluyo, Handoyo Djoko; Budiatmo, Agung (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
This research aim to determine the effect of brand equity to decision of purchasing and the effect of price, product quality, and brand equity to decision of buying. The sampling technique used was purposive sampling. In this research the sample amounted to 100 respondent with characteristic that consumer of Waroeng Makan â€œSpesial Sambalâ€ that have bought minimal twice in six month late, able and want to be interviewed. Data was analyzed with validity and Â reliability, the coefficient of determination test, and test of significance with the t test and F test with program SPSS version 16.0 for windows. The result of research showed that there is a positive effect and significant between price and decision of purchasing amount 12,8%. Product quality have a positive effect and significant to decision of purchasing amount 8%. Brand equity have a positive effect and significant to decision of purchasing amount 33,5%.